The Role of Demographic Factors in Predicting Organizational Commitment Among Security Employees - Avcı, Abdülkadir; ERDEM , Ramazan (European Journal of Multidisciplinary Studies, 2022)
The construct, “organizational commitment” has been a subject of interest for a long time for the people who study the organizational psychology. Employees’ organizational commitment is a complex matter and there are many factors which affect the organizational commitment of employees. Even though the organization has important role in it, demographic and individual characteristics of employees have also significant influence on organizational commitment. In this study a cross-sectional survey was conducted using a convenience sample of 336 security employees in a military organization to establish possible relationship between organisational commitment and important demographic variables (nationality, rank, gender, age, education, marital status, tenure). The data obtained by the survey were analysed using the SPSS 21.0 package program. In statistical analyses, T-test and variance (ANOVA) analyses were used. The results of the data showed that affective commitment of employees who had been working between 11-15 years was significantly differentiated from those of working years over 25 years. The results of this study also showed that officers had more normative commitment than civilians and the supervisors had less normative commitment than non-supervisors. The analysis also showed that males and younger employees differed significantly in normative commitment than their female counterparts and older employees. However, no statistically significant difference was found in education and marital status.